Efficacy of Semiannual Single Fixed Low-Dose Rituximab Therapy in Steroid-Dependent Minimal Change Nephrotic Syndrome: A Case Series - Ryosuke Usui (Case Reports in Nephrology and Dialysis, 2018)
The frequency of using rituximab to treat refractory nephrotic syndrome has recently been increasing, and the conventional dose of rituximab used to treat it, 375 mg/m2 body surface area once weekly for 4 weeks, has been modelled on the chemotherapy regimen for B-cell non-Hodgkin’s lymphoma. The dose and intervals of rituximab in refractory nephrotic syndrome remain controversial. Clear lymphoma cell hyperplasia is seen in lymphoma patients, but not in nephrotic syndrome patients. Since we thought that it might be possible to reduce the dose of rituximab if only used for the purpose of depleting CD20-positive B cells in nephrotic patients’ peripheral blood, we tried semiannually with a single fixed rituximab dose of 100 mg/body, and a complete remission was attained in 3 cases without treatment with prednisolone or cyclosporine. Our report strongly suggests considering appropriate dose and interval of rituximab therapy in the treatment of steroid-dependent nephrotic syndrome.